ANALISIS PROFITABILITAS DAN LIKUIDITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT SIANTAR TOP Tbk - Dedi Suhendro (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
The purpose of this study is to assess the company's financial performance at PT Siantar Top Tbk with the use of financial ratio analysis during the period of 2011-2015. The financial ratios used are profitability and liquidity. Profitability ratios at PT Siantar Top Tbk show an efficient company performance in terms of average Net Profit Margin ratio as it is above the industry average (time series). The Return On Asset (ROA) ratio is also efficient because the company's net profit tends to increase and is above the industry average (time series). The average value of the Return On Equity (ROE) ratio below the industry average (time series) for financial performance is said to be inefficient. Analysis of Liquidity Ratio (Likuidity Ratio) when viewed from the Current Ratio indicates the condition of corporate liquidity is not good, the calculation of the average Current Ratio is below the industry average (time series) for financial performance is said ILLikuid (not good). The calculation of the average Quick Ratio is below the industry average (time series) for financial performance is said IL Liquid (not good).